2020
DOI: 10.2337/db20-0585
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Role of Leucine-Rich α-2-Glycoprotein 1 in Cutaneous Wound Healing Under Normal and Diabetic Conditions

Abstract: Delayed wound healing is commonly associated with diabetes. It may lead to amputation and death if not treated in a timely fashion. Limited treatments are available partially due to the poor understanding of the complex disease pathophysiology. Here, we investigated the role of leucine-rich α-2-glycoprotein 1 (LRG1) in normal and diabetic wound healing. First, our data showed that LRG1 was significantly increased at the inflammation stage of murine wound healing, and bone marrow–derived cells served as a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 47 publications
1
50
0
1
Order By: Relevance
“…And Kumagai et al [22] have revealed that LRG1 is produced from heart-infiltrating myeloid cells in MI hearts and that LRG1 ameliorates cardiac remodeling with angiogenesis in the subacute phase after MI. Liu et al [27] have found that the angiogenic effect of LRG1 is required for normal wound healing and LRG1 is predominantly produced by the wound-infiltrating CD11b + myeloid cells. In line with these findings, our previous [24] and present study showed that LRG1 was mainly located at renal tubules and some inflammatory cells in kidney including CD4 + , CD11b + , and CD11c + cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And Kumagai et al [22] have revealed that LRG1 is produced from heart-infiltrating myeloid cells in MI hearts and that LRG1 ameliorates cardiac remodeling with angiogenesis in the subacute phase after MI. Liu et al [27] have found that the angiogenic effect of LRG1 is required for normal wound healing and LRG1 is predominantly produced by the wound-infiltrating CD11b + myeloid cells. In line with these findings, our previous [24] and present study showed that LRG1 was mainly located at renal tubules and some inflammatory cells in kidney including CD4 + , CD11b + , and CD11c + cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LRG1 has different roles in different conditions. Liu et al [27] has found that LRG1 is significantly increased at the inflammation stage of murine wound healing, and LRG1 deletion causes impaired immune cell infiltration, re-epithelialization, and angiogenesis, leading to delayed wound healing. But on the other hand, LRG1 was markedly induced in diabetic wounds in both humans and mice, and LRG1-deficient mice were resistant to diabetes-induced delay in wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we provide new insight into the cause of dysfunctional vessel growth in tumors and show that LRG1 is a significant angiopathic factor capable of disrupting the normal angiogenic process and contributing to the pro-oncogenic microenvironment of primary tumors. Under normal conditions the principal source of LRG1 is the liver where it may serve as an acute phase protein ( 39 ) involved in wound healing ( 40 ). In many diseases, however, LRG1 is induced locally in tissue lesions by the vascular endothelia and, in the case of cancer, by surrounding tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In endothelial cells (EC), LRG1 promotes angiogenesis by tipping the balance of TGFβ1 signalling toward the ALK1/Smad1,5,8 pathway, which is dependent on the presence of the type III TGF β1 receptor endoglin [7]. Besides its role in retinal angiogenesis [7], LRG1 has been linked to abnormal angiogenesis in glomerular [8], ischemic brain [9], cornea [10], and diabetic wounds [11]. Neovascularization plays an essential role in tumour expansion [12] and tumour vasculature provides a route of transportation for tumour cell dissemination [13].…”
Section: Introductionmentioning
confidence: 99%